Insight into the late Holocene sea-level changes in the NW Atlantic from a paraglacial beach-ridge plain south of Newfoundland - Billy, Julie; Robin, Nicolas; Hein, Christopher J.; Certain, Raphaël; Fitzgerald, Duncan M. (Geomorphology, 2015)
International audience Constructional sedimentary features can provide insight into past changes in relative sea-level (RSL) in regions where traditional bio-stratigraphic markers are absent. The paraglacial beach-ridge plain at Miquelon-Langlade, located 50 km south of Newfoundland, is an example of a well-preserved regressive barrier. Initiation of this plain correlates with a decrease in the rate of RSL rise (from + 4.4 mm/yr to ~ 1.3 mm/yr) at around 3000 years ago. It developed under conditions of normal regression during a period of slow RSL rise (< 1.3 mm/yr). The barrier is composed of two oppositely prograding mixed sand-and-gravel beach-ridge systems, which evolved contemporaneously along two open coasts. The growth of these features reflects high rates of sediment influx that was sourced from the erosion of proximal glacigenic sediment (moraines) and reworked alongshore and across-shore by wave action. The combination of stratigraphic (ground-penetrating radar and sediment cores), topographic (RTK-GPS) and chronologic (optically stimulated luminescence, OSL) data provide a detailed understanding of the constructional history of the plain. The well-defined contact between coarse-grained, wave-built facies and overlying aeolian deposits is used to demonstrate the dominant influences of RSL change in the development of the barrier system and produce a RSL curve over the period of its formation. A net increase of 2.4 m in the surface elevation of wave-built facies is observed across the plain, corresponding to the increase in mean sea-level during its formation. Coupled with OSL dates, trends in elevation of the wave-built facies across the plain are used to reconstruct the relative sea-level history during this period. Acknowledging the uncertainties inherent in the method applied in this study, three distinct periods of sea-level rise can be distinguished: (1) an increase from 2.4 to 1 m below modern MSL between 2400 and 1500 years (average rate of + 1.3 mm/yr); (2) relatively stable or slowly ...